1993
DOI: 10.1016/0014-5793(93)80421-p
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the PABA peptide hydrolase alpha subunit (PPHα) from human small intestine and its expression in COS‐1 cells

Abstract: PABA peptide hydrotase (PPH) from human enterocytes is comprised of two subunits, alpha and beta. PPHa is over 70% identical to meprin, a protease isolated from mouse and rat kidney. The enzyme shows a modular organization in that it contains an astacin protease domain, an adhesive domain, an EGF-like domain, and a putative C-terminal membrane spanning domain. Expression of a chimeric meprin-PPHa cDNA in COS-1 cells led to the synthesis of immature, transport-incompetent homodimers. In addition, complex glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…Lepageet al (1992a); SpAN, Reynoldset al (1992);SuBMP, Hwangetal. (1994);HuBMP-I, Wozneyet al (1988); XeBMP-I, Maeno et al (1993); DrTld (Drosophila tolloid), Shimell et al (1991); HuTld, Takahara et al (1994); MuBMP-I, Fukagawa et al (1994); DrTlr-l (Drosophila rolloid-relared-l), Nguyen et al (1994); Mu meprin-a, ; Rt meprin-a, Corbeil et al (1992); Hu meprin-a, Dumermuth et al (1993);Mu meprin-0, Gorbeaet al (1993); Rt meprin-0, Johnson and Hersh (1992); Hu meprin-0, Sterchi (pers. comm bonds.…”
Section: Js Bond and R J Beynonmentioning
confidence: 99%
See 1 more Smart Citation
“…Lepageet al (1992a); SpAN, Reynoldset al (1992);SuBMP, Hwangetal. (1994);HuBMP-I, Wozneyet al (1988); XeBMP-I, Maeno et al (1993); DrTld (Drosophila tolloid), Shimell et al (1991); HuTld, Takahara et al (1994); MuBMP-I, Fukagawa et al (1994); DrTlr-l (Drosophila rolloid-relared-l), Nguyen et al (1994); Mu meprin-a, ; Rt meprin-a, Corbeil et al (1992); Hu meprin-a, Dumermuth et al (1993);Mu meprin-0, Gorbeaet al (1993); Rt meprin-0, Johnson and Hersh (1992); Hu meprin-0, Sterchi (pers. comm bonds.…”
Section: Js Bond and R J Beynonmentioning
confidence: 99%
“…Studies with transfected meprin cDNAs have led to a similar picture of meprin organization (Milhiet et al, 1994). When fulllength meprin CY transcripts were transfected into COS-I, 293, or MDCK (Madin Darby canine kidney) cells, meprin CY subunits were secreted, and very little remained associated with cells (Corbeil et al, 1993;Dumermuth et al, 1993). In contrast, transfection of full-length (3 subunit transcripts led to plasma membrane-bound (3 subunits (Johnson & Hersh, 1994).…”
Section: Oligomeric Structure and Membrane Associationmentioning
confidence: 99%
“…Meprin, also termed endopeptidase 24.1 8 is expressed in microvillus membranes of epithelial cells in kidney proximal tubules and small intestine of mouse and rat [ 13 -151, and has also been found to be excreted in a soluble form in mouse urine [16]. In contrast, PPH has so far only been identified in the human intestine [17], although a similar enzyme activity has recently been found in human kidney also [18].…”
mentioning
confidence: 99%
“…Expression studies in COS-1 (Simian virus 40 transformed African green monkey kidney) and MDCK (Madin-Darby canine kidney) cells have shown that rat meprin a and a mouse meprin-PPHn chimera form disulphide linked homodimers [ 17,19,201 that are secreted in a complex glycosylated form. However, the cell-associated a subunit was an immature and transport-incompetent protein which did not reach the cell surface.…”
mentioning
confidence: 99%
“…Meprin is a membranal metalloendoproteinase found in the intestinal and renal brush-border membranes of the mouse (14,15), rat (16 -18), and man (19,20). Meprins belong to the astacin family of endopeptidases (21)(22)(23)(24) and are usually composed of two types of subunits, ␣ and ␤, that exist as homo-and heterotetramers bound to each other through disulfide bridges (25,26).…”
mentioning
confidence: 99%